Placenta Previa Percreta: A Case Report of Successful Management via Conservative Surgery. (17th January 2013) - Canonico, Silvia; Arduini, Maurizio; Epicoco, Giorgio; Luzi, Giuseppe; Arena, Saverio; Clerici, Graziano; Affronti, Giuseppe
Abstract : Placenta percreta is one of the most serious complications of placenta previa and is frequently associated with severe obstetric hemorrhage usually necessitating hysterectomy. We present a case of placenta previa percreta diagnosed by ultrasound and magnetic resonance imaging techniques, in which we accomplished conservative management of postpartum hemorrhage. The management we propose includes the following steps: preventive catheterization of the descending aorta via transhumeral access; Stark cesarean delivery; uterotonics drugs; Affronti endouterine square hemostatic sutures; intrauterine application of Bakri balloon and partial filling with 100 mL of normal saline; B Lynch suture, hysterorrhaphy, and filling a Bakri balloon with up to 500 mL of normal saline; reversible radiological embolization; and/or surgical ligation of the uterine arteries. The bleeding stopped following placement of Affronti sutures combined with external (B-Lynch suture) and internal (Bakri balloon) uterine compression. Our experience indicates that this conservative method can be considered an option in the management of selected cases of pregnancy at high risk for intrapartum hemorrhage.